ISOLASI PROTEIN DARI AMPAS KECAP DENGAN CARA EKSTRAKSI SODA - Utami, Lucky Indrati (REKAPANGAN, 2009)
Seed of Soy represent food-stuff having rate of protein enough is highÂ That Â is Â about Â 35% . Â Serve Â the Â purpose Â of Â raw Â material Â of Â making Â taste Â in Â ferment Â , Â where Â ketchupÂ represent penyedap of food liked by most Indonesia society .Â Â  Â  Â  Â  Â  Â Protein there Â are Â in Â ketchup only Â about Â 7 % , Â the Â rest Â of Â medium Â follow Â castaway Â in Â dregs Â .Â Therefore Â in this Â research Â require Â to Â be Â re-taken Â the Â between time Â of Â squealer Â with Â protein Â rate Â ,Â relation Â between temperature Â with Â protein Â rate Â . Â protein Â which Â is Â there Â are Â in Â dregs Â taste Â to Â be Â usedÂ upon which mixture in food process flesh and milk . Upon which fastener and emulsifier in product -Â flesh product .Â In this research will be learned relation between time of squealer with protein rate , relation Â betweenÂ temperature with protein rate. Â Â  Â  Â  Â  Â  Variable Â remain Â to Â used Â this Â research Â is Â sieve size and Â squealer Â speed , Â while Â for Â the Â variableÂ change used by temperature at spanning : 30 â 70oC , squealer time and at spanning : 15 - 75 minute. Â Â  Â  Â  Â  Â  Intention of this research is to determine optimum time and temperature , in order to got rate ofÂ highest protein in flour of ketchup dregst Â Â  Â  Â  Â  Â From result of this research [is] obtained [by] rate of highest protein when squealerÂ Â 60 minute and temperature 60 Â°C, that is equal to 64,85 %.Keyword : Ketchup Dregs , Ekstraction , Protein .